The endothelium permeability after bioresorbable scaffolds implantation caused by the heterogeneous expression of tight junction proteins. (December 2022) - Huang, Junyang; Ge, Shuang; Luo, Desha; Du, Ruolin; Wang, Yang; Liu, Wanling; Wang, Guixue; Yin, Tieying
Abstract: As one of the main functions of vascular endothelial cells, Vascular permeability is determined by four tight junction proteins (TJPs): Zonula Occludens-1 (ZO-1), Claudin-5, Occludin and Tricellulin. The barrier function of blood vessels will be reconstructed after they are damaged by endothelial mechanical injuries caused by vascular interventions. In this study, the effects of balloon expansion (transient mechanical injury) on four TJPs and vascular permeability were compared with those of poly- l -lactic acid bioresorbable scaffolds (BRSs) implantation (continuous mechanical stimulation). We found that BRSs do not affect vascular permeability, while the recovery of vascular barrier function was found to be only related to the mechanical injuries and repair of endothelium. Mechanical stimulation affects and accelerates the recovery process of vascular permeability with the heterogeneous expression levels of TJPs induced after BRSs implantation. Different TJPs have different sensitivity to different loyal mechanical stimuli. ZO-1 is more sensitive to shear stress and tension than to static pressure. Occludin is sensitive to static pressure and shear stress. Tricellulin is more sensitive to tension stretching. Compared with the other three TJPs, Claudin-5 can respond to mechanical stimulation, with relatively low sensitivity, though. This difference in sensitivity determines the heterogeneous expression of TJPs. Mechanical stimulation of different kinds and strengths can also cause different cell morphological changes and inflammatory reactions. As an important element affecting endothelial function, the mechanical factors emerging after BRSs implantation are worthy of more attention. Graphical abstract: Image 1 Highlights: The repair of vascular permeability is directly related to the type of vascular injuries, while BRSs implantation has little effect on vascular permeability. Transient and persistent mechanical stimulation is the main reason to influence the expression of TJPs. Heterogeneous expression of TJPs caused by their different sensitivity to the form of mechanical stimuli.